Amanah Saham Nasional Berhad (ASNB) Ipoh / Mohamad Syabani Ashraf Mohamad Ali - Mohamad Ali, Mohamad Syabani Ashraf (Universiti Teknologi MARA, Perlis, 2023)
My six-month industrial training at Amanah Saham Nasional Berhad (ASNB) Ipoh was summarized in this report. My industrial training began on August 29,2022 and will end on February 10, 2023. Puan Noor Sharida Badri Shah, my supervisor, and Puan Fan Siew Mey, an ASNB’s officer who gave and shared a lot of information with me, were the people who supported me the most during my internship. In ASNB Ipoh, there were two departments in this office which are Branch Management & Supervision Department (JPPC) and Sales Marketing Operation Department (SMOD). I am assigned to the Sales Marketing Operation Department (SMOD) but sometimes I have been directed in helping the branch department. The goal is to gain more knowledge and experience about this company. Furthermore, this report discusses the Value Added of Intellectual Capital Efficiency: A Comparative Analysis of Employee Provident Fund (EPF) and LembagaTabung Haji. The analysis seeks to assess the value added of Intellectual Capital in several areas by using the Value-Added Intellectual Coefficient (VAIC)’s method. Ten consecutive years are used in calculating the data.